CHINA - CENTRAL AND EASTERN EUROPE COOPERATION IN THE CONTEXT OF THE RISE OF CHINA: A REALIST PERSPECTIVE - Yiğit Yamanlar (Ankara Avrupa Çalışmaları Dergisi)
Following the 2008–2009 global financial crisis, China began to engage in power competition in the CEE region for its economic and political interests. The EU regards the increase of Chinese influence in the CEE as a threat to its integrity and the interests of EU member states. The study argues that the basis of China-CEE cooperation is based on a realist thought that serves China's rise, aims to maximize China's economic power, and prioritizes Chinese interests. The study presents the basic motivations underlying China's involvement in power competition in the CEE, the impact of China’s growing influence in the CEE on the dominant actors in the region, such as the EU and Germany, and also their attitudes towards China-CEE cooperation from a realist perspective.